2017
DOI: 10.1016/j.jcct.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Vectors through a cross-sectional image (VCI): A visualization method for four-dimensional motion analysis for cardiac computed tomography

Abstract: Background Cardiac computed tomography (CT) has the potential for fully four-dimensional (4D for 3D plus time) motion analysis of the heart. We aimed at developing a method for assessment and presentation of the 4D motion for multi-phase, contrast-enhanced cardiac CT data sets and demonstrating its clinical applicability. Methods Four patients with normal cardiac function, old myocardial infarction (OMI), takotsubo cardiomyopathy, and hypertrophic cardiomyopathy (HCM) underwent contrast-enhanced cardiac CT f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Located at the center of the visual cortex, the LING and the cuneus are in charge of visual function processes ( 48 ). A randomized controlled trial confirmed that visual dysfunction may exist in sVCI and regular ophthalmological exams can help improve the quality of life ( 49 ). Our findings were consistent with the clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Located at the center of the visual cortex, the LING and the cuneus are in charge of visual function processes ( 48 ). A randomized controlled trial confirmed that visual dysfunction may exist in sVCI and regular ophthalmological exams can help improve the quality of life ( 49 ). Our findings were consistent with the clinical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There was a synergistic effect between the networks. When the DMN and ECN are abnormal, the VN will also be functionally damaged ( 49 ). As for the compensatory increase in the VN in the later period, more experiments are needed to prove this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile real-time 3D echocardiographic images were employed by Suematsu and his colleagues [37] to guide beating heart atrial septal defect closure. Zhang et al [38] designed a stereoscopic cardiac image dynamic visualization platform to provide cardiologists with real-time feedback regarding heart anatomical information, Kidoh et al [39] reported a rendering method for motion analysis of cardiac computed tomography, and the impact of visualizing 4D flow on diagnosis and surgical planning was demonstrated by Christopher et al [40]. However, these software platforms were limited to local computers without Internet-based synchronization or medical information streaming, so were unsuitable for collaborative analysis and treatment planning [41].…”
Section: Related Workmentioning
confidence: 99%